The Influence of Size, Third-Party Funds, and Dividend Policy on the Profitability of Islamic Banks in Asia - Hermawan, Bagus; Jaya, Tiara Juliana (Universitas Islam Kadiri, 2025)
This study aims to analyze the impact of bank size, third-party funds (TPF), and dividend policy on the profitability of Islamic banks in Asia. The study population consists of the 128 largest Islamic banks in the world that are listed and publish annual financial reports for the period 2019-2023, and the sample includes 15 Islamic banks from 11 countries in Asia with the largest assets. The sampling technique used is purposive sampling. The analysis method employed is panel regression, using EViews 10 software. The results indicate that bank size has a positive and significant impact on profitability, TPF has a negative and significant impact, while dividend policy does not have a significant effect on profitability. These findings provide important implications for fund management, increasing economies of scale, and resource allocation to support the sustainable growth of the Islamic banking industry in Asia.